Crystal sructure of ethyl(3-methyl-7-coumaryloxy)acetate - Koca, Murat; Kirilmií, Cumhur; Arici, Cengiz; Tuncer, Hülya; Heinemann, Frank W. (Japan Society for Analytical Chemistry, 2005)
C14H14O5, contains four molecules in the monoclinic unit cell. The coumarin moiety forms a dimmer structure by ?-? interaction around the inversion centre. The distance between two coumarins is 3.4241(3)Å. The structure is stabilized by one intramolecular and five intermolecular hydrogen-bonding interactions. 2005 © The Japan Society for Analytical Chemistry.